2017
DOI: 10.1186/s12917-017-1207-0
|View full text |Cite
|
Sign up to set email alerts
|

Sample size and number of outcome measures of veterinary randomised controlled trials of pharmaceutical interventions funded by different sources, a cross-sectional study

Abstract: BackgroundRandomised controlled trials (RCTs) are a key component of the veterinary evidence base. Sample sizes and defined outcome measures are crucial components of RCTs.To describe the sample size and number of outcome measures of veterinary RCTs either funded by the pharmaceutical industry or not, published in 2011.MethodsA structured search of PubMed identified RCTs examining the efficacy of pharmaceutical interventions. Number of outcome measures, number of animals enrolled per trial, whether a primary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…A documentation of a sample size calculation was presented in only few articles. This is in accordance with the findings of Wareham et al, 26 where only 14.3% reported a sample size calculation and Giuffrida 16 with 22.0%. In addition, in most studies the number of animals was low.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A documentation of a sample size calculation was presented in only few articles. This is in accordance with the findings of Wareham et al, 26 where only 14.3% reported a sample size calculation and Giuffrida 16 with 22.0%. In addition, in most studies the number of animals was low.…”
Section: Discussionsupporting
confidence: 93%
“…The low prevalence of rare diseases might also play a role. The median sample size seems to have improved as it is 31 according to this study and 30 animals within the trial of Wareham et al 26 A limitation of this study is that we did not recalculate the power of the studies. A recalculation, however, would not have been reasonable for most studies because main target parameters were not specified for most studies.…”
Section: Discussionmentioning
confidence: 77%
“…The minimum sample size was exceeded and a post-hoc power calculation confirmed the study was adequately powered to detect a difference between the groups. Sample size and power calculation is actually considered a crucial factor in the reliability of RCT results although it has been shown to be still vastly underreported in the veterinary trials literature [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple outcomes were included in almost all (91/100) clinical trials related to health and production in livestock (Sargeant et al, 2009), with a mean of 9.5 (range 1 to 41) outcomes per trial. Wareham et al, (2017) reported that the median number of outcomes in trials in cattle (dairy or beef) was 5.5, with a range of 1 to 36. Although it may increase the efficiency of data collection, having multiple outcomes has important implications for study design and analysis.…”
Section: Determining the Number Of Outcomes To Include In A Trialmentioning
confidence: 99%